Analysis of mesoscale patterns in relation to synoptic conditions over an urban Mediterranean basin - Kassomenos, P.a c; Flocas, H.A.b d; Lykoudis, S.a c; Petrakis, M.a c (Theoretical and Applied Climatology, 1998)
In this study day by day synoptic conditions are classified over the Attica peninsula for a period of sixteen years. Eight synoptic categories which are demonstrated to be statistically distinct are selected with respect to the atmospheric circulation in the lower troposphere. Furthermore, a methodology is proposed to classify the mesoscale patterns for the same period on the basis of surface wind measurements, and this distinguishes eleven distinct mesoscale categories. In general, the frequency analysis reveals that the anticyclonic circulation dominates while the weak mesoscale flows prevail, with preference in May and June. A day by day cross tabulation of the synoptic flow patterns with the mesoscale categories is then performed in order to identify the association of the synoptic conditions with the mesoscale flow regime. It was found that the synoptic conditions at the level of 850 hPa are closely related to the observed surface local flows and therefore it is suggested that the synoptic categories can be used for the identification of the most favourable mesoscale atmospheric circulation.
Keywords: anticyclone; atmospheric dynamics; circulation; Mediterranean; mesoscale; Synoptic meteorology; troposphere